Rhinosporidiosis: Various Presentations and Different Sites - Saumendra Nath Bandopadhyay; Utpal Jana; Gautam Bandopadhyay; Tapas Kumar Majhi; Shubhrakanti Sen; Soumyarup Das; Ipsita Mandal (Bengal Journal of Otolaryngology and Head Neck Surgery, 2015)
Introduction Rhinosporidiosis commonly affects nasal mucosa but may have varied presentations depending upon the site of involvement.